Evidence for a giant parrot from the Early Miocene of New Zealand. (30th August 2019) - Worthy, Trevor H.; Hand, Suzanne J.; Archer, Michael; Scofield, R. Paul; De Pietri, Vanesa L.
Abstract : Insular avifaunas have repeatedly spawned evolutionary novelties in the form of unusually large, often flightless species. We report fossils from the Early Miocene St Bathans Fauna of New Zealand that attests to the former existence of a giant psittaciform, which is described as a new genus and species. The fossils are two incomplete tibiotarsi from a bird with an estimated mass of 7 kg, double that of the heaviest known parrot, the kakapo Strigops habroptila . These psittaciform fossils show that parrots join the growing group of avian taxa prone to giantism in insular species, currently restricted to palaeognaths, anatids, sylviornithids, columbids, aptornithids, ciconiids, tytonids, falconids and accipitrids.